2003
DOI: 10.1093/genetics/165.4.1687
|View full text |Cite
|
Sign up to set email alerts
|

TheESS1Prolyl Isomerase and Its SuppressorBYE1Interact With RNA Pol II to Inhibit Transcription Elongation inSaccharomyces cerevisiae

Abstract: Transcription by RNA polymerase II (pol II) requires the ordered binding of distinct protein complexes to catalyze initiation, elongation, termination, and coupled mRNA processing events. One or more proteins from each complex are known to bind pol II via the carboxy-terminal domain (CTD) of the largest subunit, Rpb1. How binding is coordinated is not known, but it might involve conformational changes in the CTD induced by the Ess1 peptidyl-prolyl cis/trans isomerase. Here, we examined the role of ESS1 in tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 72 publications
1
38
0
Order By: Relevance
“…Another SPOC domain protein, RBM15, regulates N 6 -methyladenosine (m6A) RNA modification, splicing, and mRNA export, and inhibits myeloid differentiation 76 79 . The yeast PHF3 homolog Bye1 negatively regulates early stages of transcription elongation 32 , 80 , while Arabidopsis SPOC proteins FPA and BORDER regulate 3′end pausing and processing 81 , 82 . Future characterization of SPOC domains from different proteins and species will address some key questions: is the SPOC domain a universal phospho-serine recognition module, how is the choice of binding partners determined, and how exactly do they regulate gene expression to ensure proper differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another SPOC domain protein, RBM15, regulates N 6 -methyladenosine (m6A) RNA modification, splicing, and mRNA export, and inhibits myeloid differentiation 76 79 . The yeast PHF3 homolog Bye1 negatively regulates early stages of transcription elongation 32 , 80 , while Arabidopsis SPOC proteins FPA and BORDER regulate 3′end pausing and processing 81 , 82 . Future characterization of SPOC domains from different proteins and species will address some key questions: is the SPOC domain a universal phospho-serine recognition module, how is the choice of binding partners determined, and how exactly do they regulate gene expression to ensure proper differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Yeast genetic studies have previously suggested competition between the yeast homolog Bye1 and Dst1 (TFIIS) for Pol II binding 32 , 34 but this model has never been experimentally tested. Using in vitro reconstitution, we showed that PHF3 competes with TFIIS for binding to Pol II and thereby impedes the rescue of backtracked Pol II.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ess1 was originally identified in Saccharomyces cerevisiae , where it was shown to be essential for cell growth (), and later demonstrated to be a PPIase ( , ). In S. cerevisiae , Ess1 (ScEss1) binds the carboxy-terminal domain (CTD) of the large subunit of RNA polymerase II ( , ) and controls multiple stages of transcription, including initiation and elongation ( , ). Ess1 orthologs have been identified in nearly all eukaryotic organisms that have been examined, including flies, humans, and other pathogenic fungi ( ).…”
mentioning
confidence: 99%
“…(CTD) of the large subunit of RNA polymerase II (21,22) and controls multiple stages of transcription, including initiation and elongation (23,24). Ess1 orthologs have been identified in nearly all eukaryotic organisms that have been examined, including flies, humans, and other pathogenic fungi (25)(26)(27)(28)(29).…”
mentioning
confidence: 99%